# |
ODE |
Mathematica |
Maple |
\[
{}{y^{\prime }}^{6} = \left (y-a \right )^{4} \left (y-b \right )^{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{4} \left (y-b \right )^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{5} \left (y-b \right )^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{5} \left (y-b \right )^{4} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left ({y^{\prime }}^{6}+3 y^{4}+3 y^{2}+1\right ) = a^{2}
\] |
✗ |
✗ |
|
\[
{}2 \sqrt {a y^{\prime }}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) \sqrt {y^{\prime }} = a \left (1+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+{y^{\prime }}^{2}} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\sqrt {a^{2}+b^{2} {y^{\prime }}^{2}}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}a \sqrt {1+{y^{\prime }}^{2}}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}a x \sqrt {1+{y^{\prime }}^{2}}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {\left (a \,x^{2}+y^{2}\right ) \left (1+{y^{\prime }}^{2}\right )}-y y^{\prime }-a x = 0
\] |
✓ |
✓ |
|
\[
{}a \left (1+{y^{\prime }}^{3}\right )^{{1}/{3}}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y^{\prime }\right )+x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}a \cos \left (y^{\prime }\right )+b y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y^{\prime }\right )+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (y^{\prime }\right )+\cos \left (y^{\prime }\right ) = y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (x +\sin \left (y^{\prime }\right )\right ) = y
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) \sin \left (x y^{\prime }-y\right )^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) \left (\arctan \left (y^{\prime }\right )+a x \right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{\prime }-y}-{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+x y^{\prime }+a = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+x y^{\prime }+a = y
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+x y^{\prime }+a +b y = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+4 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+a \left (x y^{\prime }-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}a \left (\ln \left (y^{\prime }\right )-y^{\prime }\right )-x +y = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y^{\prime }\right )+y^{\prime }-y \ln \left (y\right )-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \ln \left (y^{\prime }\right )-\left (1+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \ln \left (y^{\prime }+\sqrt {a +{y^{\prime }}^{2}}\right )-\sqrt {1+{y^{\prime }}^{2}}-x y^{\prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}\ln \left (\cos \left (y^{\prime }\right )\right )+y^{\prime } \tan \left (y^{\prime }\right ) = y
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (1+{y^{\prime }}^{2}\right ) = R^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {a y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}}
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-5 y^{\prime }+6 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-\frac {a^{2}}{x^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = \frac {1-x}{x}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+\frac {2 x y^{\prime }}{y}-1 = 0
\] |
✓ |
✓ |
|
\[
{}y = a y^{\prime }+b {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x = a y^{\prime }+b {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = \sqrt {1+{y^{\prime }}^{2}}+a y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x = \sqrt {1+{y^{\prime }}^{2}}+a y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {\sqrt {1+{y^{\prime }}^{2}}}{x} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (1+{y^{\prime }}^{2}\right )^{3}-a^{2} = 0
\] |
✓ |
✓ |
|
\[
{}1+{y^{\prime }}^{2} = \frac {\left (x +a \right )^{2}}{2 a x +x^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {b^{2}-a^{2} {y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+x \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+a x \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}x -y y^{\prime } = a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = a \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x +y^{2}-y^{2} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y-\frac {1}{\sqrt {1+{y^{\prime }}^{2}}} = x +\frac {y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}}
\] |
✓ |
✓ |
|
\[
{}y-2 x y^{\prime } = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\frac {-x y^{\prime }+y}{y^{2}+y^{\prime }} = \frac {-x y^{\prime }+y}{1+x^{2} y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{4}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x y y^{\prime }-6 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (y-1-x^{2}\right ) y^{\prime }-x \left (y-1\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}8 y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}16 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{5}-{y^{\prime }}^{4} y+\left (x^{2}+1\right ) {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+\left (y^{2}+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-y y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y = \left (1+y^{\prime }\right ) x +{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = 2 y^{\prime }+\sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 y-1\right )^{2} {y^{\prime }}^{2} = 4 y
\] |
✓ |
✓ |
|
\[
{}y = -x y^{\prime }+x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}2 y = {y^{\prime }}^{2}+4 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \left (3-4 y\right )^{2} {y^{\prime }}^{2} = 4-4 y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x^{4} y^{\prime }+8 x^{3} y = 0
\] |
✗ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) \left (x -y\right )^{2} = \left (x +y y^{\prime }\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (y^{\prime }\right ) = x +y
\] |
✓ |
✓ |
|
\[
{}\sin \left (x^{\prime }\right )+y^{3} x = \sin \left (y \right )
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2} = 4 y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 9-y^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 y^{\prime }+4 y = 4 x -1
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-4 y^{\prime }-12 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}1+{y^{\prime }}^{2} = \frac {1}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}1+{x^{\prime }}^{2} = \frac {a}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (y^{\prime }+y\right ) = x \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }+y\right )^{2} = y^{\prime } y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-3 x y y^{\prime }+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|